TINJAUAN YURIDIS PELAYANAN KANTOR PERTANAHAN DALAM HAL PENDAFTARAN TANAH DI KOTA PALEMBANG - Yonani; Rusniati (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
One of the main objectives of the UUPA is to lay the foundation for providing legal certainty regarding land rights for all people, by having registered land on every land throughout Indonesia, it means that it has provided the foundations for realizing legal certainty regarding land rights. for the Indonesian people, especially for the peasant people as a society, their rights can be protected. The services of the land office in terms of land registration in Palembang City are in accordance with the BPN service standards listed in the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 1 of 2010 concerning Service Standards and Land Arrangements, where Article 3 reads: The purpose of this regulation is to realize certainty law, openness and public service accountability. To further increase public awareness about land registration because not all people understand the importance of land registration and also many do not have legal guarantees of certainty over land rights, because of these two things a conflict and land dispute arises that stems from lack of evidence of rights in the hands of the community in the form of certificates. Settlement through the courts is also ineffective, especially for people with a weak economy.